Who's who in contemporary gay and lesbian history
1 online resource.
Keywords: Provides a comprehensive modern biographical survey of homosexuality in the Western world. Among those included are:* controversial political activists - Peter Tatchell; Guy Hocquenghem; Harvey Milk* pop icons - David Bowie; k d lang; Boy George* groundbreaking artists, writers and filmmakers - Pier Paolo Pasolini; Derek Jarman; David Hockney* intellectuals who have shaped and changed the modern understanding of sexuality - Michel Foucault; Simone de Beauvoir; Alfred Kinsey* over 500 entries - clear, informative and enjoyable to read - build up a superbly thorough overview of gay and lesbian life in our time.